2004
DOI: 10.1124/jpet.103.064105
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Angiotensin-Converting Enzyme and Neutral Endopeptidase 24.11 Inhibition on Plasma Extravasation in the Rat

Abstract: The effect of angiotensin-converting enzyme (ACE) and neutral endopeptidase (NEP) inhibition on microvascular plasma leakage (extravasation) was evaluated in a rat model. Progressive inhibition of ACE using captopril caused increased extravasation when lung ACE was inhibited by Ͼ55%. In contrast, the selective inhibition of renal NEP by Ͼ90% using ecadotril did not increase extravasation. In NEP-inhibited rats, extravasation produced by the ACE inhibitors captopril and lisinopril was markedly enhanced. The dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
(38 reference statements)
1
20
0
1
Order By: Relevance
“…We have demonstrated that captopril-induced plasma extravasation in this model was enhanced by concomitant inhibition of NEP (Sulpizio et al, 2004). These findings seem consistent with the report that C1 inhibitor deficiency in humans leads to spontaneous angioedema (Markovic et al, 2000).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…We have demonstrated that captopril-induced plasma extravasation in this model was enhanced by concomitant inhibition of NEP (Sulpizio et al, 2004). These findings seem consistent with the report that C1 inhibitor deficiency in humans leads to spontaneous angioedema (Markovic et al, 2000).…”
supporting
confidence: 81%
“…Thus, it was evident that, for some unexplained reason, GW796406 had inherently less liability to increase extravasation than did omapatrilat. Interestingly, GW796406 also had less liability to increase extravasation than did combinations of ACEIs and ecadotril, which significantly increased plasma extravasation in spite of much lower levels of ACE inhibition than that produced by GW796406 (Sulpizio et al, 2004). This difference between the two agents was not observed at the higher dose regimen.…”
Section: Omapatrilat and Gw796406 Plasma Extravasation In Rat 1311mentioning
confidence: 75%
See 1 more Smart Citation
“…This effect has been attributed to firstly the rapid increase in bradykinin and its metabolite BK-8 by simultaneously blocking both BK degrading pathways and secondly by potentially a direct effect of the agent to promote extravasation. 13 Based on these findings and, in particular, the incidence of this potentially life threatening side effect it appears unlikely that omapatrilat will become routine medication for hypertension, especially in the Afro-American population.…”
Section: Clinical Evidence For a Superior Cardiovascular Effect Of Acmentioning
confidence: 99%
“…Indeed, omapatrilat has recently been shown to induce extravasation in high doses. 13 As the various ACE/NEP inhibitors differ in their ability and relative potency to inhibit ACE versus NEP this may not only influence the magnitude of kinin production but also the antihypertensive, cardio vascular and antifibrotic effects.…”
mentioning
confidence: 99%